PENGARUH PEMBELAJARAN BERBASIS SCIENCE, TECHNOLOGY, ENGINEERING, MATHEMATICS TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII SMP NEGERI 32 PADANG - Jatmiko, Raisa Febriana (Jurnal Edukasi dan Penelitian Matematika, 2025)
Everyone should be competent in problem solving, especially those involving mathematics. The objectives of this research were to (1) describe how these skills are developed through STEM-based learning and (2) determine whether STEM-based learning outperforms more conventional forms of education. Participants in this study were randomly selected from grade eight at SMP Negeri 32 Padang. The research utilized the Nonequivalent Posttest Only Control Group Design as its research format. The skills under study were assessed through quizzes and tests. Descriptive statistics and hypothesis testing were used to test the data. Such skills are honed in STEM classes, according to descriptive statistics. Learning in STEM fields was associated with an increase in these skills, according to hypothesis testing.Keywords– Mathematical Problem Solving Skills, STEM Based Learning, Direct Learning